PENGENALAN ANIMASI KEPADA SISWA PAKET B PKBM AL-HAMRA - perdananto, agung; Mirza, Anis; Rofiq, Nur (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
In the world of education, currently information technology is something that has a very important role, apart from being used as a medium of information and communication in school activities, it also functions as a learning medium that attracts students' interest. One of the learning media that can be used in learning is information technology-based learning media. The use of information technology as a learning media can take the form of images, animation, video, audio, CAI (Computer Assisted Instruction) programs, simulation programs, etc. Information technology-based learning media is very good to apply during learning because students are more interested in technology-based media so that students will be more enthusiastic during learning activities.The media used in learning activities in kindergarten must be chosen carefully and should be able to depict the values ​​that shape the student's identity. In the world of education today, especially learning for children, animation has the concept of fun learning (learning while playing), animation is considered quite effective as a learning medium. Video games can also be said to be computer games created using programming and animation techniques. In general, animation provides a system for controlling object movements and settings and designs that can be adjusted. Apart from being aimed at entertaining, animation can also help attract children's interest in learning and hone children's way of thinking. Keywords: Learning Media, Animation, Students